2013
DOI: 10.2319/111812-883.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of the golden proportion in the evaluation of facial esthetics

Abstract: Objective: To demonstrate if one or more golden relationships between different measurements of the human face exist. Materials and Methods: To make our measurements, we used three-dimensional (3D) stereophotogrammetry, which has proved to be the ''gold standard'' in the field of facial anthropometry. We obtained 3D stereophotogrammetric facial acquisitions of 400 healthy young adult subjects, then had them scored by an Evaluation Jury. Each subject received an esthetic evaluation ranging from 0 to 40. Individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 22 publications
0
52
2
Order By: Relevance
“…[7,8]. Some authors have stated that the golden proportion is not present in attractive faces, natural aesthetic smiles and is not suitable to relate to the successive width of the maxillary anterior teeth [9][10][11]. Due to the contradiction in the above mentioned studies, there is confusion for both the clinician and technician.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8]. Some authors have stated that the golden proportion is not present in attractive faces, natural aesthetic smiles and is not suitable to relate to the successive width of the maxillary anterior teeth [9][10][11]. Due to the contradiction in the above mentioned studies, there is confusion for both the clinician and technician.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, patients with skeletal dysmorphia are more asymmetrical than healthy subjects without malocclusions [9,16], as shown in the current analysis that allowed to localize those parts of the face showing a higher degree of left-right imbalance. The present method can, therefore, be coupled with the conventional analyses of facial esthetics [17], thus increasing the quantitative description of the patient, and helping in treatment planning and monitoring of follow up.…”
Section: Discussionmentioning
confidence: 99%
“…The golden ratio was used to achieve balance and beauty in many Renaissance paintings and sculptures. The golden ratio also appears in da Vinci's Vitruvian Man and the Mona Lisa (Baker and Woods, 2001;Rossetti et al, 2013). The silver ratio is an analog of the more well-known golden ratio which arises in many mathematical and geometric expressions.…”
Section: Introductionmentioning
confidence: 99%
“…Jefferson (2004) stated that, any deviation of human face from golden proportion can result in the development of facial abnormalities and disorders. A study by Rossetti et al (2013) showed that, the ratios between 3D facial distances were not related to attractiveness and most facial ratios were different from the golden ratio. In recent years, various studies in the general population and orthodontic patients have tried to establish the importance of golden proportions in determining facial attractiveness and esthetics, but with conflicting results.…”
Section: Introductionmentioning
confidence: 99%